hPMSCs inhibit the expression of PD-1 in CD4(+)IL-10(+) T cells and mitigate liver damage in a GVHD mouse model by regulating the crosstalk between Nrf2 and NF-κB signaling pathway - Zhang, Aiping (Stem Cell Res Ther, 2021)
BACKGROUND: The activation of T cells and imbalanced redox metabolism enhances the development of graft-versus-host disease (GVHD). Human placenta-derived mesenchymal stromal cells (hPMSCs) can improve GVHD through regulating T cell responses. However, whether hPMSCs balance the redox metabolism of CD4(+)IL-10(+) T cells and liver tissue and alleviate GVHD remains unclear. This study aimed to investigate the effect of hPMSC-mediated treatment of GVHD associated with CD4(+)IL-10(+) T cell generation via control of redox metabolism and PD-1 expression and whether the Nrf2 and NF-κB signaling pathways were both involved in the process. METHODS: A GVHD mouse model was induced using 6–8-week-old C57BL/6 and Balb/c mice, which were treated with hPMSCs. In order to observe whether hPMSCs affect the generation of CD4(+)IL-10(+) T cells via control of redox metabolism and PD-1 expression, a CD4(+)IL-10(+) T cell culture system was induced using human naive CD4(+) T cells. The percentage of CD4(+)IL-10(+) T cells and their PD-1 expression levels were determined in vivo and in vitro using flow cytometry, and Nrf2, HO-1, NQO1, GCLC, GCLM, and NF-κB levels were determined by western blotting, qRT-PCR, and immunofluorescence, respectively. Hematoxylin-eosin, Masson’s trichrome, and periodic acid-Schiff staining methods were employed to analyze the changes in hepatic tissue. RESULTS: A decreased activity of superoxide dismutase (SOD) and a proportion of CD4(+)IL-10(+) T cells with increased PD-1 expression were observed in GVHD patients and the mouse model. Treatment with hPMSCs increased SOD activity and GCL and GSH levels in the GVHD mouse model. The percentage of CD4(+)IL-10(+) T cells with decreased PD-1 expression, as well as Nrf2, HO-1, NQO1, GCLC, and GCLM levels, both in the GVHD mouse model and in the process of CD4(+)IL-10(+) T cell generation, were also increased, but NF-κB phosphorylation and nuclear translocation were inhibited after treatment with hPMSCs, which was accompanied by improvement of hepatic histopathological changes. CONCLUSIONS: The findings suggested that hPMSC-mediated redox metabolism balance and decreased PD-1 expression in CD4(+)IL-10(+) T cells were achieved by controlling the crosstalk between Nrf2 and NF-κB, which further provided evidence for the application of hPMSC-mediated treatment of GVHD.